Longitudinal Relationship Between Hearing Aid Use and Cognitive Function in Older Americans. Issue 6 (10th April 2018) - Maharani, Asri; Dawes, Piers; Nazroo, James; Tampubolon, Gindo; Pendleton, Neil; ,
Abstract : Objectives: To test whether hearing aid use alters cognitive trajectories in older adults. Design: US population‐based longitudinal cohort study Setting: Data were drawn from the Health and Retirement Study (HRS), which measured cognitive performance repeatedly every 2 years over 18 years (1996–2014). Participants: Adults aged 50 and older who who took part in a minimum of 3 waves of the HRS and used hearing aids for the first time between Waves 4 and 11 (N=2, 040). Measurements: Cognitive outcomes were based on episodic memory scores determined according to the sum of immediate and delayed recall of 10 words. Results: Hearing aid use was positively associated with episodic memory scores (β=1.53, p<.001). Decline in episodic memory scores was slower after (β=–0.02, p<.001) than before using hearing aids (β=–0.1, p<.001). These results were robust to adjustment for multiple confounders and to attrition, as accounted for using a joint model. Conclusions: Hearing aids may have a mitigating effect on trajectories of cognitive decline in later life. Providing hearing aids or other rehabilitative services for hearing impairment much earlier in the course of hearing impairment may stem the worldwide rise of dementia.